2022
DOI: 10.1038/s41380-022-01661-0
|View full text |Cite
|
Sign up to set email alerts
|

The serotonin theory of depression: a systematic umbrella review of the evidence

Abstract: The serotonin hypothesis of depression is still influential. We aimed to synthesise and evaluate evidence on whether depression is associated with lowered serotonin concentration or activity in a systematic umbrella review of the principal relevant areas of research. PubMed, EMBASE and PsycINFO were searched using terms appropriate to each area of research, from their inception until December 2020. Systematic reviews, meta-analyses and large data-set analyses in the following areas were identified: serotonin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
216
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 415 publications
(315 citation statements)
references
References 74 publications
2
216
0
7
Order By: Relevance
“…The monoamine hypothesis plays an important role in the pathogenesis of depression, which believes that depression is closely related to the low level of monoamine such as NE and 5-HT in brain. Although the serotonin hypothesis of depression is still influential, a recent systematic umbrella review of the principal relevant areas of research on whether depression is associated with lowered serotonin concentration or activity suggested that peripheral serotonin levels have no correlation with depression and might not be useful as a biomarker ( Frank et al, 2000 , Moncrieff et al, 2022 ). The clinical relevance of peripheral monoamine measure warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The monoamine hypothesis plays an important role in the pathogenesis of depression, which believes that depression is closely related to the low level of monoamine such as NE and 5-HT in brain. Although the serotonin hypothesis of depression is still influential, a recent systematic umbrella review of the principal relevant areas of research on whether depression is associated with lowered serotonin concentration or activity suggested that peripheral serotonin levels have no correlation with depression and might not be useful as a biomarker ( Frank et al, 2000 , Moncrieff et al, 2022 ). The clinical relevance of peripheral monoamine measure warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…At a practical level, the MG theory of depression could help treatment move beyond the serotonin hypothesis and the use of Specific Serotonin Reuptake Inhibitors (SSRI's) which is currently controversial (Moncrieff et al, 2022). Serotonin is implicated in rats' depression-like responses to hypergravity environments (Abe et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, successfully applying a reductionist approach "often depends on on using the higher order phenomena to guide the search for lower level explanations and to recognize an adequate explanation when it has been found" (Kirmayer & Gold, 2012, p. 309). This might be a reason why the "chemical imbalance" hypotheses never seem to hold up to experimental scrutiny, in spite of being commonly held view by health professionals and layperson alike (Moncrieff et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The depressogenic effect of amine-depleting drugs, such as reserpine, and the use of serotonin reuptake inhibitors to treat mood disorders, including major depressive disorder, led to favoring this neurotransmitter in mechanistic explanations of mood regulation (Cowen & Browning, 2015;Vaswani et al, 2003). While this monoaminergic theory of depression has long been viewed as overly simplistic (Cowen, 2008;Moncrieff et al, 2022), the role of 5-HT in different manifestations of distress has expanded considerably. In part, this is due to the application of selective serotonin reuptake inhibitors (SSRIs) to treat more and more disorders (Vaswani et al, 2003); currently, there is evidence of low-to-moderate quality of positive effect of SSRIs in the treatment of depressive disorders (Arroll et al, 2009;Purgato et al, 2014;Wilkinson & Izmeth, 2016), obsessive-compulsive disorder (Soomro et al, 2008), various anxiety disorders (Bighelli et al, 2018;Williams et al, 2017), and post-traumatic disorder (Williams et al, 2022).…”
Section: Introductionmentioning
confidence: 99%